Al-Qatt Al-Asiri aesthetics and its role in enriching the contemporary art production - Al Qahtani, Yousry Saeed Mohammed (Journal of Humanities & Social Sciences, 2019)
The study aims to identify Al-Qatt Al-Asiri aesthetics and highlighting its importance in enriching contemporary artistic production. It also aims to identify the artistic and aesthetic values that characterize Al-Qatt Al-Asiri. The researcher used the analytical descriptive approach to describe the particulars of Al-Qatt Al-Asiri, and to analyze some of artworks for some of Aseer region artists. The study concluded that Aseer region and its folk decorations, represented in Al-Qatt Al-Asiri, has artistic and aesthetic values, which participate in updating distinct works of the visual arts. This study sought to ensure the originality and heritage through inspiring by Al-Qatt Al-Asiri and employing it in a contemporary form. The study recommended establishing an academy, under the umbrella of the General Authority for Culture, specialized in learning the style of Al-Qatt Al-Asiri by popular female artists, to maintain this style and disseminate it within the community.
Keywords: Al-Qatt Al-Asiri; contemporary artistic production